FEASIBILITY OF CORN FARMING ON DRY LAND IN PRINGGABAYA DISTRICT EAST LOMBOK REGENCY: - - rini endang; Muhammad Anwar; Rizal Ahmadi (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
This study aims to examine the feasibility of corn farming on dry land in Pringgabaya District. Improvements in technology and corn cultivation systems through increasing farmer knowledge are expected to increase productivity which in turn increases farmers' income in corn cultivation in dry land. Research activities are carried out in several stages, including: (i) site survey, identifying problems, and preparing proposals; (ii) data collection, data tabulation, and data analysis; (iii) draw conclusions and recommend the results of the study. The recommendations generated from this research are in the form of information on components and types of corn farming according to location specifications on dry land in Pringgabaya. District. Based on the results of the study, it can be seen that the income earned in corn farming is Rp. 6,137,729 /LLG or Rp. 6.134,871/Ha. And based on the calculation of the R/C ratio of corn farming on dry land in Pringgabaya District, the R/C ratio was 1.9. This shows that corn farming in Pringgabaya District, East Lombok Regency is feasible.